Unmet needs for cataract surgery in Spain according to indication criteria. Evaluation through a simulation model. Issue 7 (24th June 2008) - Comas, M; Román, R; Cots, F; Quintana, J M; Mar, J; Reidy, A; Minassian, D; Castells, X; ,
Abstract : Aims: Despite the increase in cataract surgery rates, the volume of unmet needs for this type of surgery in the population is substantial due to ageing and widening of the indication criteria. Our objective was to assess future trends in needs for cataract surgery according to different scenarios of indication criteria. Methods: A discrete-event simulation model was built for the population aged 50 years or older in five regions of Spain (45.7% of the population). Different scenarios of worse eye visual acuity thresholds for indication criteria were compared. Data from the North London Eye Study were used to project the baseline needs for surgery onto the study population. The surgery rate of each region was calculated using the Minimum Data Set. The model used data for the year 2003 and the simulation horizon was 5 years. Results: The volume of need predicted for the year 2008 when scenarios of 0.5 (20/40) and 0.4 (20/50) visual acuity thresholds were used was 69 214 and 51 315 surgeries needed per million inhabitants, respectively. However, unmet needs decreased when a 0.3 (20/70) threshold was used. The increment in the cataract surgery rate needed to prevent the cataract backlog from increasing was 60% for a 0.5 threshold and 50% for a 0.4 threshold. Conclusion: Application of indication criteria following current guidelines would substantially increase unmet needs for surgery in the next 5 years.